Comprehensive review of single stage switched boost inverter structures. Issue 12 (6th July 2021) - Palanidoss, Sriramalakshmi; Thazhathu, Sreedevi Vellithiruthi; Bhaskar, Mahajan Sagar; Kannan, Ramani; Baboli, Payam Teimourzadeh
Abstract: Single‐stage switched boost inverter (SBI) with buck‐boost capability finds wide applications in renewable energy systems (RES). This paper aims at a comprehensive topological review of various single stage SBI circuits. The boosting techniques of SBI include switched inductor, switched capacitor, and transformer assisted switches. Each SBI derived structure has its own merits and demerits depending on the applications. The performance evaluation of SBIs, based on various perspectives like boost factor, voltage stress across active devices, passive elements count, DC link voltage, switching losses, voltage gain, and efficiency, are also discussed. A suitable modulation strategy is used to obtain the desired boosted and inverted ac output voltage in one stage SBI. Different modulation strategies adopted for SBIs are also included at the end of the topological review. This topological review's contribution enlightens the researchers in selecting appropriate SBI with effective modulation strategies suitable for renewable energy applications. Besides, the benefits and shortcomings of these converters are discussed in detail.